2015
DOI: 10.1097/scs.0000000000001280
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Quality of Life in Survivors of Head and Neck Cancer Who Have had Defects Reconstructed With Radial Forearm Free Flaps

Abstract: The purpose of our study was to investigate (by postal questionnaire) the long-term quality of life (QoL) in Chinese patients who have had resections of head and neck cancer and immediate reconstruction by radial forearm free flaps. We performed a retrospective questionnaire survey and case series in the Affiliated Tumor Hospital of Zhengzhou University. The subjects were consecutive patients treated for head and neck cancers during a 13-year period. The patients completed the University of Washington Quality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(21 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…Swallowing function often deteriorated throughout time (Data S1, Appendix 3, table 2). [13][14][15][17][18][19]21,22,24,26,28,30,31,[34][35][36][37]39,41,42 Mean EORTC QLQ-H&N35 scores for the domains swallowing, speech, and sticky saliva were relatively comparable between studies. For the domain of swallowing, scores ranged approximately from 20 to 30, for speech from 20 to 25, and for sticky saliva around 40 points.…”
Section: Eating Swallowing and Speech Functionmentioning
confidence: 88%
See 4 more Smart Citations
“…Swallowing function often deteriorated throughout time (Data S1, Appendix 3, table 2). [13][14][15][17][18][19]21,22,24,26,28,30,31,[34][35][36][37]39,41,42 Mean EORTC QLQ-H&N35 scores for the domains swallowing, speech, and sticky saliva were relatively comparable between studies. For the domain of swallowing, scores ranged approximately from 20 to 30, for speech from 20 to 25, and for sticky saliva around 40 points.…”
Section: Eating Swallowing and Speech Functionmentioning
confidence: 88%
“…14,29,45 The study of Li et al showed that long-term survivors of HNC reported more favorable anxiety and mood scores, which may be explained by a longer disease-free period. 22 Anxiety and mood scores varied between the included studies, related to flap type and donor-site morbidity. Patients with a PMMF reconstruction generally reported poorer mood scores compared with patients with a free flap reconstruction, possibly due to worse speech functioning and more shoulder symptoms with the PMMF.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations